Reduce, manage or cope: a review of strategies for training school staff to address challenging behaviours displayed by students with intellectual/developmental disabilities. Issue 3 (19th June 2014) - Stoesz, Brenda M.; Shooshtari, Shahin; Montgomery, Janine; Martin, Toby; Heinrichs, Dustin J.; Douglas, Joyce
Abstract : Members of a knowledge translation and exchange (KTE) research team assessed the training needs of the teaching staff at a school for individuals with intellectual/developmental disabilities (IDD). In response to this need, KTE researchers retrieved peer‐reviewed articles for training staff working with individuals with IDD who exhibit challenging behaviours. These articles were categorised according to the following training content: (1) interventions designed to reduce the frequency of challenging behaviours; (2) appropriate ways to manage challenging behaviours in the moment to promote safety for all parties and/or to terminate the ongoing behaviour; and/or (3) procedures or perspectives relevant to coping with or ameliorating the negative impacts of challenging behaviours on staff. We then examined the training methods (teaching strategies, training duration) involved in teaching the content and assessed the effectiveness of these programmes. Overall, we found that effective training programmes consisted of workshops, practica and feedback on specific skill performance. Some forms of brief training were effective for increasing staffs' knowledge/skills and reducing the frequency of challenging behaviour.